Aprovechamiento de la cáscara de camarón para la obtención de quitosano y su potencial aplicación en la remoción de metales pesados, provincia de Cotopaxi en el periodo 2022-2023. - Chancusig Sarzosa, Jessica Elizabeth (2023)
The expansion of the shrimp trade in Ecuador has strengthened the economy of many vulnerable groups, however, it has also led to an increase in solid waste, which in most of our country is not adequately managed. The main objective of this research was to take advantage of shrimp shells to obtain chitosan and use this by-product for heavy metal removal treatments such as arsenic (As) and Copper (Cu) in contaminated water. The chitosan synthesis was carried out by separation processes of minerals, proteins, decolorization, and deacetylation, and the chitosan obtained was continuously characterized by means of infrared spectrometry by Fourier transforms. In order to determine the heavy metal removal capacity of the chitosan obtained, a controlled test was carried out in which three samples contaminated with arsenic were prepared at concentrations of 20 ppm, 40 ppm, and 60 ppm (evolution samples), and a replica of each contaminated sample was also carried out (control samples), therefore only one g of chitosan was added to the evolution samples; This treatment was kept under supervision for a total of 144 hours, during this time changes in pH and conductivity could be observed in both the evolution and control samples, however, the concentration decreased drastically only in the evolution samples, therefore it was determined that the arsenic and copper removal capacity of the chitosan obtained average 99.85%. Finally, it is established that the chitosan obtained from the red shrimp Farfantepenaeus brevirostris shell is efficient as a biosorbent because its arsenic removal capacity is 99.86% and copper 99.85%. In addition, it is recommended to use chitosan in procedures or solutions that present color, because it is also a good color absorbent.